Between Daily Routine and Violent Protest Interpreting the Technicity of Action - Wolff, Ernst (De Gruyter, 2021)
Human action has a technical dimension. This book is a hermeneutic and social theoretical interpretation of how acquired capabilities and the means of action together shape the technicity of action. The enactment of individual, group, and institutional action is examined, drawing on situations ranging from daily routine to the dilemmas of ethics and politics. This study opens a window on the technicity of responsibility and the tools of critique.